Strong shareholders, weak outside investors. Issue 2 (3rd July 2018) - Gutiérrez, María; Sáez Lacave, Maribel
ABSTRACT: We consider the corporate governance challenge of protecting outside investors in listed, controlled firms. We argue that outside investors in European listed firms with controlling shareholders are poorly protected compared to US investors because the distinct European approach to the protection of investors, based on empowering active shareholders rather than shielding passive investors, is not well suited for controlled, listed firms. This approach translates into a lack of definition and development of specific fiduciary duties of the controlling shareholders towards market investors. Moreover, European jurisdictions have developed strong voice rights for active shareholders, which tend to play in favour of controlling shareholders and organised minorities but are not effective for protecting passive investors and limit their exit options. This explains why shareholder protection in European jurisdictions can be considered high, while outside investors' protection can be considered low at the same time, generating a 'strong shareholders, weak outside investors' problem.